Atividade física e fatores associados em idosos de uma cidade do sul do Brasil: um estudo transversal - Muhl, Marluce de Oliveira (2019)
The increase in life expectancy and the aging of the world's population is a new demographic reality that must be accompanied by quality of life. Knowing the characteristics and transformations that occur in the aging process becomes increasingly important, particularly investigating the impact of general health related to other diseases. Physical activity is a determining factor and can reduce mortality, improve health conditions and functional capacity over 60 years, acting as a valuable preventive in the quality of life gain. Objective: To evaluate the level of physical activity and associated factors in an elderly population in a southern Brazilian city. Method: This was a cross-sectional, household-based observational study that targeted individuals aged 60 years or older in residential households in the city of Veranópolis (RS). Physical activity was assessed using the short version IPAQ, as well as a structured questionnaire that included: demographic data, socioeconomic status, marital status, oral hygiene habits, general health behavior, health history, tooth appearance, halitosis, history. of implants, quality of life related to oral health and classify the elderly in TMD or not. Results: There were 282 participants in the study age fax, where 49.6% were considered active elderly. The present study identified a high prevalence of inactive elderly that was directly related to age and number of health problems. The present dissertation is extruded with Introduction, Literature Review, Scientific Production, in the form of a scientific article entitled: “PHYSICAL INACTIVITY AND FACTORS ASSOCIATED WITH ELDERLY OF A SOUTH BRAZIL CITY: A TRANSVERSAL STUDY”. appendices and appendices. It is noteworthy that studies relating physical activity and associated factors are significant, as they may characterize determining factors for a successful aging.